Attractiveness of Kuala Tahan National Park as perceived by domestic and international ecotourists - Syed Alias, Sharifah Nur Hidayah (2012)
The purpose of this study was to assess the attractiveness of Pahang National Park at Kuala Tahan as perceived by the domestic and international tourists in Malaysia. This study was also set to determine which attributes or types of attraction were perceived as the most and the least important in tourists’ decision to visit Kuala Tahan National Park and to compare such perception between the domestic and international tourists. In addition, the overall perceived attractiveness of the park was measured and differences in opinion between the domestic and international tourist was gathered. By using the multi attribute model, thirteen attractions were evaluated, which were oral history, local culture and lifestyle, diversity of flora, diversity of fauna, architectural of building at Kuala Tahan National Park, nature trails, shopping opportunity, canopy walkway, caves, stream and rapids, fishing, Mount Tahan and adventure activities. Findings indicated that the adventure activities appeared as the most important attraction in decision making, followed by nature trails and diversity of fauna. While shopping opportunity was rated as the least important in the tourists’ travel decision making, followed by the architectural of building at Kuala Tahan, and the local culture and lifestyle. Between the domestic and international tourists, domestic tourists preferred adventure activities as their most important attraction, followed by Mount Tahan and canopy walkway, while international tourists tend to prefer diversity of fauna, followed by nature trail and diversity of flora as the most important attraction at Kuala Tahan National Park. Domestic tourist had evaluated Kuala Tahan National Park as attractive while for international tourist had evaluated it as quit attractive. From the segmentation result, it can be concluded that there were not much differences on the respondent profile between the groups (Pessimist, Neutral and Optimist) based on their individual attractiveness evaluation in term of nationality and gender. It was also concluded that the most important attraction in tourist decision making to visit Kuala Tahan National Park was not necessarily also the most available in the park and this might effect on tourist travel experience and satisfaction. Through this study a better understanding on the concept of destination choice among tourist in making decision when traveling will provide the park management with sound alternatives in attracting more tourists and at the same time suggesting ways for preserving the natural resources. Assessing the attractiveness is a fundamental for managing and marketing ecotourism destinations as this will measure the destination performance in meeting the need and preferences of tourist.